SRY gene mutation in Rattus norvegicus induced by various time exposure of mobile phone - ARNI AMIR; ERYATI DARWIN; AHMAD ZULVA JUNIARTO (Society for Indonesian Biodiversity, 2018)
Amir A, Darwin E, Juniarto AZ. 2018. Effects of mobile phone exposure to SRY gene in Rattus norvegicus. Biodiversitas 19: 802-808. Mobile phones are low power radio devices, which transmit and receive radio frequency radiation in the microwave spectrum ranging from 900-1,800 MHz through an antenna used closely to the user’s head. Radiation destructs living tissue by altering structure of cell and damaging the DNA, damaging of genetic material in reproductive cells causes mutations and affecting to the next generation. The genetic database of mutation in human SRY gene has been collected and had the correlation between mutation and the occurrence of sex development disorder (translocation). However, the study focussing on SRY gene mutation to the exposure of mobile phone has not been studied, yet. This study was aimed to investigate the effect of various time exposure of mobile phone toward the characteristic of SRY gene fragments in Rattus norvegicus. Experimental research with randomized post test only control design was conducted on 20 Wistar aged 2-3 months with 200-250 grams of weight. Samples were divided into four groups, with three treatment groups based on radiation exposure time (30, 60, and 90 minutes), and one group as control group (without treatment) for 60 days. Following exposure, DNA was isolated from blood of rat, and amplified with a pair of SRY primer set. Positive DNA of SRY gene was assessed by sequencing the genes and determining the mutations. There were three single nucleotide polymorphism (SNP) of SRY gene in histidine 38 glutamine, (CAT> CAG), proline 76 threonine (CCT >ACT) and leucine 102 leucine (CTG >TTG). Long duration of radiation exposure for 90 minutes increased the risk of SRY gene mutation.